ANXIETY OF CLAYTON REFLECTED IN JOBY HAROLD’S AWAKE MOVIE (2009): A PSYCHOANALYTIC APPROACH - Rosanti, Elisa Fitriana (2011)
The object of the study is a movie AWAKE directed by Joby Harold. The study is to reveal how is anxiety reflected in Awake movie directed by Joby Harold published in 2009. The objective of the study is to analyze the structural elements in the movie and to analiyze the anxiety of the main characters using psychoanalytic. The researcher employs the descriptive qualitative research as a type of the research. The data sources divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of Awake and the secondary data source is biography of character. The method of collecting data are observation and library research. The technique of analyzing data is descriptive. Based on the analysis, the researcher draws two conclusions, first based on the structural analysis, Joby Harold wants to deliver moral message that Love of a woman is not greather than love a mother to her child”. From the structural analysis, it shows that each of the structural element are interlated to each other. Second, based on the psychoanalytic analysis, Joby Harold reflects anxiety is caused by the contradiction of his id, ego and superego which cause the disharmony of hopes and fact in his life.